IMPACT OF CALOTHRIX SP. A PROMOTIVE BIOFERTILIZER ON GROWTH PERFORMANCE OF BARLERIA PRIONITIS IN POT CULTURE: Life Science-Agricultural Science - HUSSAIN BAKSHI, SAJAD; AHMAD LONE, SHABIR; TAFAZUL RASHID, MALIK; DAR, SHAHIJAHAN; AHMAD SHAH, KHURSHEED (International Journal of Life Science and Pharma Research, 2012)
As the problem of chemical fertilizers can be a restraining factor for agriculture development and crop production increases, the alternative methods have to be sought out and the present techniques discussed in this work appears to be a very suitable way to combat the pressing need of the nitrogen fertilizers using these simple nitrogen fixing cyanobacteria, which are low costing, high efficiency biofertilizers of today. An attempt was made to test a promotive biofertilizer- Calothrix Sp. on growth performance of Barleria prionitis in pot culture and the results revealed that all the growth parameters viz; Root length, Shoot length, Number of leaves, Fresh weight of leaves, Chlorophyll a content and Chlorophyll b content of Barleria prionitis treated with Calothrix Sp. and urea as compared with the initial values were found maximum as compared to control.